Ayurveda prophylaxis and intervention for COVID-19 Pandemic - Kavita Chambyal; Sanjeev Sharma; Suman Sharma (Wolters Kluwer Medknow Publications, 2020)
Introduction: Novel coronavirus named SARS-CoV-2 is causing a series of acute atypical respiratory symptoms. It is an Aupsargika Vyadhi and virus is transmittable between humans and has been declared as pandemic worldwide. The number of death toll continues to rise and there is no specific treatment till now. Initially, the pathology and symptoms of the disease pertain to the respiratory system and according to Ayurveda, this can be correlated with Pranavaha Srotas Vyadhi and the management should be like Shwasa roga. Objective: To provide critical evaluation of prophylaxis and interventions involved in Ayurveda for COVID-19. Data Source: Ayurveda Samhita, text, Journals, Internet etc. Review Method: Literary review. Discussion: On the basis of COVID-19 clinical features and present understanding of the pathogenesis, it mainly seems to be associated with Kapha and Vata Dosha vitiation. Nidana Parivarjana (not coming in contact with vyadhita such as maintain social distancing, use of mask, and proper hand hygiene); use of herbal, mineral, and herbo-mineral drugs; and Panchkarma procedures such as Nasya (Nasal application), Abhyanga, and Hitakara Ahara according to Desha, Kala, Ritu, etc., play important role in the prevention and management of this new disease. Conclusion: COVID-19 seems to be associated with vitiation of Kapha and Vata Dosha, and use of Ayurvedic principles and drugs can improve and regulate the immunity which helps in preventing the diseases. If disease manifestation occurs, then it can also be managed by Ayurveda interventions.